Amphotericin B resistance in Leishmania mexicana: alterations to sterol metabolism and oxidative stress response - Alpizar-Sosa, Edubiel A.; Ithnin, Nur Raihana; Wenbin, Wei; Pountain, Andrew W.; Weidt, Stefan K.; Donachie, Anne M.; Ritchie, Ryan; Dickie, Emily A.; Burchmore, Richard J. S.; Denny, Paul W.; Barrett, Michael P. (Public Library of Science, 2022)
Amphotericin B is increasingly used in treatment of leishmaniasis. Here, fourteen independent lines of Leishmania mexicana and one L. infantum line were selected for resistance to either amphotericin B or the related polyene antimicrobial, nystatin. Sterol profiling revealed that, in each resistant line, the predominant wild-type sterol, ergosta-5,7,24-trienol, was replaced by other sterol intermediates. Broadly, two different profiles emerged among the resistant lines. Whole genome sequencing then showed that these distinct profiles were due either to mutations in the sterol methyl transferase (C24SMT) gene locus or the sterol C5 desaturase (C5DS) gene. In three lines an additional deletion of the miltefosine transporter gene was found. Differences in sensitivity to amphotericin B were apparent, depending on whether cells were grown in HOMEM, supplemented with foetal bovine serum, or a serum free defined medium (DM). Metabolomic analysis after exposure to AmB showed that a large increase in glucose flux via the pentose phosphate pathway preceded cell death in cells sustained in HOMEM but not DM, indicating the oxidative stress was more significantly induced under HOMEM conditions. Several of the lines were tested for their ability to infect macrophages and replicate as amastigote forms, alongside their ability to establish infections in mice. While several AmB resistant lines showed reduced virulence, at least two lines displayed heightened virulence in mice whilst retaining their resistance phenotype, emphasising the risks of resistance emerging to this critical drug.